GIS-material for the archaeological project: Burial and settlement remains at Fålåsa - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
By request of the County Administrative Board the Swedish National Heritage Board's contract archaeology division, UV Öst, has performed a preliminary investigation with the property Fålåsa 5:8, Vikingstad, Rappestad parish, Linköping city. The reason was the local planning of the area by the municipality. The results of the survey (area 2) and the preliminary investigation (area 3) show that there are archaeological remains in both areas. Previously unknown settlement remains, such as post holes, hearths and pits, were discovered in three places within the survey area. Area 3 was located in close connection to the burial ground RAÄ 17, and both features, such as hearths and cooking pits, and destroyed graves (stone settings) were found here. UV Öst suggests further archaeological excavation in case the areas covering archaeological sites, or bordering to sites that have not been delimited, are to be developed.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the survey was to determine whether the area contains any unmarked archaeological remains that can be affected by the development works. The purpose of the preliminary investigation was to determine the extent and type of possible remains close by the burial ground.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
På uppdrag av Länsstyrelsen i Östergötlands län har Riksantikvarieämbetet UV Öst utfört en arkeologisk utredning, etapp 2 samt arkeologisk förundersökning inom fastigheten Fålåsa 5:8, Vikingstad, Rappestads socken, Linköpings kommun. Anledningen till det arkeologiska uppdraget föranleddes av Linköpings kommuns planer på detaljplaneläggning av området. Resultatet av den arkeologiska utredningen (delområde 2), samt den arkeologiska förundersökningen (delområde 3) visar att förhistoriska lämningar förekommer inom bägge delområden. Inom utredningsområdet konstaterades hittills okända fornlämningar vid tre olika punkter. Dessa innehöll boplatsanläggningar (stolphål, härdar och gropar). Förundersökningsområdet (delområde 3) låg i direkt anslutning till det registrerade gravfältet RAÄ 17 och här konstaterades såväl anläggningar (härdar och kokgropar) som rester av 4-5 förstörda gravar (stensättningar). Om en framtida exploatering kommer att ske inom fornlämningarna eller i anslutning till de områden där fornlämningarna inte i detta skede kunnat avgränsas, föreslår UV Öst att ytterligare arkeologisk undersökning bör ske.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska utredningen var att avgöra om hittills okända fornlämningar förekommer inom området och kommer att beröras av exploateringsföretaget. Den arkeologiska förundersökningen syftar till att avgöra omfattning och art av eventuella lämningar intill gravfältet.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Grav- och boplatslämningar vid Fålåsa
Keywords: Iron Age; järnålder; Bronze Age; bronsålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive